The boys in the boat : the true story of an American team's epic journey to win gold at the 1936 olympics - Brown, Daniel, 1951- (Viking, 2015)
Young Readers adaptation of the story about the 9 University of Washington rowers who qualified to compete in the 1936 Berlin Olympic Games.